2010
DOI: 10.1016/j.pain.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Central sensitization in carpal tunnel syndrome with extraterritorial spread of sensory symptoms

Abstract: Extraterritorial spread of sensory symptoms is frequent in carpal tunnel syndrome (CTS). Animal models suggest that this phenomenon may depend on central sensitization. We sought to obtain psychophysical evidence of sensitization in CTS with extraterritorial symptoms spread. We recruited 100 unilateral CTS patients. After selection to rule out concomitant upper-limb causes of pain, 48 patients were included. The hand symptoms distribution was graded with a diagram into median and extramedian pattern. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
107
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 48 publications
10
107
5
Order By: Relevance
“…The pain was found commonly and more severe in patients with mild CTS [5,6]. In our study, the severity of CTS had no correlation with proximal spread, shoulder pain, or shoulder ultrasonographic evaluation.…”
Section: Fig 1 Flowchart Of the Study Design Fms: Fibromyalgia Syncontrasting
confidence: 57%
See 4 more Smart Citations
“…The pain was found commonly and more severe in patients with mild CTS [5,6]. In our study, the severity of CTS had no correlation with proximal spread, shoulder pain, or shoulder ultrasonographic evaluation.…”
Section: Fig 1 Flowchart Of the Study Design Fms: Fibromyalgia Syncontrasting
confidence: 57%
“…These authors suggested that the continuous sensory bombardment from the median nerve might trigger cortical plastic changes. In another study, Zanette et al, (6) did not find association between proximal pain and central sensitization. They hypothesized that proximal pain may represent referred pain and activation of specific A delta and C-fibre populations may cause proximal spread in CTS.…”
Section: Fig 1 Flowchart Of the Study Design Fms: Fibromyalgia Synmentioning
confidence: 84%
See 3 more Smart Citations